The Ability of SMP N 2 Lubuk Pakam Students in using _s Inflectional Ending - Wati, Novera; Tarigan, Bahagia; Harefa, Yulianus (Modality Journal: International Journal of Linguistics and Literature, 2021)
AbstrakPenelitian ini berjudul â€œThe Ability of SMPN 2 Lubuk Pakam Students in Using -s Inflectional Endingâ€. Tujuan dari penelitian ini adalah untuk mengetahui kemampuan siswa dalam menggunakan akhiran infleksional â€“s dan kesulitan yang dihadapi oleh siswa kelas dua SMPN 2 Lubuk Pakam. Metode yang digunakan dalam penelitian ini adalah metode penelitian gabungan. Data diambil dari tes dan wawancara. Tes digunakan untuk mengukur kemampuan siswa dan wawancara digunakan untuk mengidentifikasi kesulitan siswa. Sumber data dalam penelitian ini adalah siswa kelas dua SMPN 2 Lubuk Pakam tahun ajaran 209/2020. Peneliti mengambil 0% dari populasi (29 siswa). Berdasarkan hasil analisis data, persentase siswa dengan jawaban yang benar adalah 60,06%. Artinya kempuan siswa kelas dua SMPN 2 Lubuk Pakam tergolong dalam kategori sedang. Kemampuan siswa dalam menggunakan â€“s Kata Benda Jamak memiliki persentase tertinggi (63%). Kemampuan siswa dalam â€“s Posesif memiliki persentase 56%. â€“s Orang Ketiga Tunggal memiliki persentase terendah (54%). Disimpulkan bahwa siswa kelas dua SMPN 2 Lubuk Pakam telah memahami akhiran â€“s dalam Kata Benda Jamak tetapi belum memahami akhiran â€“s dalam kata Posesif dan Orang Ketiga Tunggal. Penyebabnya dalah kurangnya pengetahuan tentang akhiran inflectional â€“s dan kosakata.Kata Kunci: Akhiran Infleksional â€“s, Kesulitan siswaAbstractThe objectives of this study are to know the studentsâ€™ ability in using â€“s inflectional endings and the difficulties faced by the students at the second year of SMPN 2 Lubuk Pakam. The method used in this research was mixed method. The data were taken from test and interview. Tes is used to measure studentsâ€™ abilities and interview to identify studentsâ€™ difficulties. The sources of data were the students at the second year of SMPN 2 Lubuk Pakam in the academic year 2019/2020. The researcher took 10% of the population (29 students). Based on the result of the data analysis, the percentage of the studentsâ€™ correct answers was 60.06% and was classified as fair category. The studentâ€™s ability in â€“s plural nouns had the highest percentage (63%). The studentâ€™s ability in â€“s possessive had the percentage of 56%. Theâ€“s third person singular had the lowest percentage (54%). It can be concluded that the second year students of SMPN 2 Lubuk Pakam had understood â€“s plural nouns but did not comprehend â€“s possessive and â€“s third person singular yet. The causes were lacking knowledge of â€“s inflectional endings and vocabulary.Keywords: -s Inflectional Endings, Studentsâ€™ Difficulties